2010
DOI: 10.1097/qad.0b013e32833ea9bc
|View full text |Cite
|
Sign up to set email alerts
|

Uridine supplementation in the treatment of HIV lipoatrophy: results of ACTG 5229

Abstract: BACKGROUND Lipoatrophy is prevalent on thymidine NRTIs (tNRTI). A pilot trial showed that uridine (NucleomaxX®) increased limb fat. METHODS A5229 was a multicenter trial in which HIV-infected individuals with lipoatrophy on tNRTI-regimens were randomized to NucleomaxX or placebo. Primary endpoint was change in limb fat from baseline to week-48. The study was powered to detect 400-gram difference between arms at week-48. A stratified Wilcoxon rank-sum test was used to assess between-arm differences. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…38 Despite these results and positive pilot data, 39 two large, randomized clinical trials have shown no benefit of a uridine-rich supplement for the treatment of lipoatrophy in HIV-infected individuals. 40,41 Similarly, the unexpected benefits of the 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitor, pravastatin, on extremity fat recovery in a small, randomized clinical trial 42 were not confirmed in two more recent randomized clinical trials. 40,43 Neither uridine nor pravastatin can, therefore, be recommended for the treatment of lipoatrophy.…”
Section: Introductionmentioning
confidence: 99%
“…38 Despite these results and positive pilot data, 39 two large, randomized clinical trials have shown no benefit of a uridine-rich supplement for the treatment of lipoatrophy in HIV-infected individuals. 40,41 Similarly, the unexpected benefits of the 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitor, pravastatin, on extremity fat recovery in a small, randomized clinical trial 42 were not confirmed in two more recent randomized clinical trials. 40,43 Neither uridine nor pravastatin can, therefore, be recommended for the treatment of lipoatrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in contrast to in vitro data, NucleomaxX supplementation did not lead to changes in fat or blood mitochondrial DNA levels 148. These promising data on lipoatrophy improvement are not fully confirmed in a larger prospective, randomized, placebo-controlled multicenter trial (ACTG study A5229) 149. In this study, the results demonstrate that in HIV lipoatrophy, despite a small increase in limb fat after 24 weeks with as-treated analysis, the effect was not sustained through 48 weeks of uridine 111,149…”
Section: Treatmentmentioning
confidence: 77%
“…The median DLQI score at baseline was 16 (range: [13][14][15][16][17][18][19]. After 12 months of treatment, the median DLQI score was 9 (range: [6][7][8][9][10][11][12][13][14], corresponding with a reduction in impairment of 43.75% (P < 0.05). 26…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Various in vitro studies of cultured adipocytes demonstrated that uridine prevented the adverse effects of pyrimidine analogs, such as mitochondrial DNA depletion and resulting adipocyte apoptosis . However, although uridine has been shown to transiently improve limb fat, it has not been shown to affect facial fat …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation